TINJAUAN YURIDIS PENGGUNAAN GANJA UNTUK KEBUTUHAN MEDIS - Muhammad Nanda Khairul; Zulfikar Jaya Kusuma; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The state guarantees the health of every citizen as stated in the 1945 Constitution, health improvement must be improved so that the situation is better than what is already there. Everyone has the right to live in physical and mental prosperity, to live and get a healthy living environment and obtain health services, Canada and other countries have legalized marijuana for health needs, marijuana was once used by Fedelis Adi Suseno for his wife's medical needs but contravenes Law Number 35 of 2009 concerning Narcotics. From this background, a problem formulation was born, namely, first, how do you regulate the use of marijuana in Indonesian legislation? Second, what is the ideal concept for medical personnel in the use of narcotic marijuana class 1 in the future? This type of research can be classified as normative-juridical research where this research is carried out on the level of vertical and horizontal synchronization, so that what is examined is to what extent the written positive law is compatible. In this study, the data sources used were secondary data with primary, secondary, and tertiary legal materials which were carried out by means of literature study.From the research results obtained that, first, marijuana is a narcotic substance that has great potential to be legalized either through discriminalization or comprehensive legalization, Canada, South Africa, Uruguay, and California each have legalized marijuana for health needs, however Indonesia has never discussed marijuana separately from various kinds of coverage related to regulatory developments, legalization and discriminalization. This has led to the emergence of social norms regarding cannabis as one of the banned plants in the world and recorded in the UN Single Convention on Narcotics and Drugs 1961. Second, in terms of economics, optimization of cannabis for medical needs is not only used to cure diseases but can also be an alternative source. country income. The author's suggestion is that countries should reduce cannabis from class 1 to lower classes so that there is a permanent legal force that guarantees the use of cannabis as a medical drug, given the UN's decision through WHO which has categorized cannabis as a medicinal plant and legalized marijuana for medical purposes.Keywords: Legalization-Cannabis-Health.